Upaya Meningkatkan Kesadaran Orang Tua tentang Hak dan Perlindungan Anak di Lembaga Pusat Pengembangan Anak (PPA) Linggang Mapan Kabupaten Kutai Barat - Mona Nimitha Balensky (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2024)
Child protection aims to guarantee the fulfillment of children's rights so that they can live, grow, develop and participate optimally in accordance with human dignity, as well as receive protection from violence and discrimination, for the sake of realizing Indonesian children who are of good quality, have noble character and prosperous. The aim of this activity is to increase parents' awareness about children's rights and protection at the Linggang Mapan Child Development Center (CDC), Linggang Bingung District, West Kutai Regency. To help partners improve parents' ability to understand and be aware of the increasing impact of violence against children, education is carried out regarding children's rights and protection. The reason for using the group counseling method or group approach is because the concept of extension is related to group counseling targets. This method is more profitable because it allows for feedback and group interaction which provides the opportunity to exchange experiences and influence the behavior and norms of its members. After carrying out activities for two weeks with two meetings with the parents of the Linggang Mapan Child Development Center (CDC) children, the author can conclude that during the process, parents can understand and comprehend what is meant by children's rights and protection by paying attention to each other's environment. a place for children to play and develop and explain to children what should be avoided while playing and socializing with other people, because violence or abuse can happen anywhere and be done by anyone, including family members.